Bead-Containing Superhydrophobic Nanofiber Membrane for Membrane Distillation - Talukder, Md Eman; Talukder, Md. Romon; Pervez, Md. Nahid; Song, Hongchen; Naddeo, Vincenzo (Membranes (Basel), 2024)
This study introduces an innovative approach to enhancing membrane distillation (MD) performance by developing bead-containing superhydrophobic sulfonated polyethersulfone (SPES) nanofibers with S-MWCNTs. By leveraging SPES’s inherent hydrophobicity and thermal stability, combined with a nanostructured fibrous configuration, we engineered beads designed to optimize the MD process for water purification applications. Here, oxidized hydrophobic S-MWCNTs were dispersed in a SPES solution at concentrations of 0.5% and 1.0% by weight. These bead membranes are fabricated using a novel electrospinning technique, followed by a post-treatment with the hydrophobic polyfluorinated grafting agent to augment nanofiber membrane surface properties, thereby achieving superhydrophobicity with a water contact angle (WCA) of 145 ± 2° and a higher surface roughness of 512 nm. The enhanced membrane demonstrated a water flux of 87.3 Lm−2 h−1 and achieved nearly 99% salt rejection efficiency at room temperature, using a 3 wt% sodium chloride (NaCl) solution as the feed. The results highlight the potential of superhydrophobic SPES nanofiber beads in revolutionizing MD technology, offering a scalable, efficient, and robust membrane for salt rejection.